ASSESSMENT OF LECTURER’S TEACHING PRACTICES, STUDENT RESEARCH-RELATED COURSE CONTENT EXPOSURE AND RESEARCH COMPETENCE AMONG POSTGRADUATE STUDENTS IN SOUTHWEST NIGERIA - Oderinwale, Titilope Abosede; Falaye, Folajogun Veronica (African Journal of Behavioural and Scale Development Research, 2024)
Abstract This study examines the influence of teaching methods employed by lecturers, the extent to which postgraduate students are exposed to research-related course content, and the research skills of postgraduate students in Southwest Nigeria. Using a correlational research design, standardised questionnaires were used to collect data from 316 postgraduate students across six universities in the region. The study utilised Pearson Product Moment Correlation (PPMC) and Multiple Regression analysis to investigate the correlations and predictive capacity of the variables. The findings revealed a moderate positive relationship between the teaching methods employed by the lecturer and student’s research competence (r = 0.36; P =0.00). Additionally, there were also a strong positive relationships between the level of course content exposure and the students' research competence (r = 0.53; P =0.00). The regression analysis revealed that the presence of research-related course content is a strong predictor of research competence (β = 0.736; p < 0.05), but teaching methods, although favourably associated, do not independently predict research competence (β = 0.249; p > 0.05). These findings highlight the significance of thorough course material and successful teaching methods in improving the research skills of postgraduate students. The paper discusses recommendations for enhancing research proficiency among postgraduate students.